Pilomyxoid astrocytoma - Azad Sheenam; Kudesia Sandip; Chawla Nitin; Azad Rajiv; Singhal Mini; Rai Suraj; Arora Pankaj (Wolters Kluwer Medknow Publications, 2010)
Pilomyxoid astrocytoma (PMA) is a recently described brain tumor. PMA shares similar features with pilocytic astrocytoma (PA), the most common central nervous system (CNS) tumor in the pediatric population, yet displays subtle histologic differences. We describe a case of PMA in a six-year-old male involving sellar and suprasellar region presenting with failure to thrive and delayed developmental milestones. The histological findings revealed a tumor composed of a monotonous population of loosely arranged cells with delicate piloid like processes, within a prominent myxoid background. The tumor lacked biphasic appearance, Rosenthal fibers, eosinophilic granular bodies and calcification that are commonly observed in classical PA. Previous studies have shown PMA to behave more aggressively than PA, with shorter progression-free survival as well as a higher rate of recurrence and CNS dissemination. Thus, recognition of PMA and its distinction from classical PA is very important.